Using digital tools to virtually plan and control a production: A case study on how digital tools can help production planning and control - Altun, Johannes; Pavlovic, Endi (My University, 2023)
Due to the growing industrial competition and constant rapid development that industries face today, manufacturers need to keep up with the technological innovations implemented in production. These technical innovations consist mostly of digitized tools that enable better production control so that more advanced products can be created based on customer requirements and needs. A digital tool that many companies choose to use is Virtual Twin, which creates a digital representation of a physical system where users can observe a manufacturing site without physically being there. However, there are developments within Virtual Twin that can increase the value for the user and this thesis proposes a framework for manufacturers on how the Virtual Twin can increase value by integrating with a new digital tool, namely the Real-Time Location System (RTLS). Through a literature review, interviews, and a case study, this thesis concludes that there are many advantages in integrating an RTLS and a Virtual Twin to create more value for users, however, this integration also brings some challenges. Another area where digital tools are used is within visual planning in the manufacturing industries. Visual planning is a concept in manufacturing where the user has the opportunity to use digital tools and strategies to visually plan something, such as a manufacturing order or planning the reconstruction of a production facility to save money and avoid unexpected problems. A digital tool commonly used in visual planning is simulation software. This thesis investigates how simulation can benefit the visual planning of a manufacturing order at Virtual Manufacturing, which is the project's case company. This is done by exploring and using different software, such as IronCad and Visual Components, which build up Virtual Manufacturing's factory and then simulate it depending on the company's orders. By doing so, the results of this thesis can support Virtual Manufacturing's visual planning for future orders, thus avoiding unnecessary costs and unexpected problems.
Keywords: digital tools, virtual twin, visual planning, simulation, real-time location system, manufacturing, industry 4.0, tracking.